Campus Policy on Tobacco Prohibition and Tobacco Use among Youth in Sub-Saharan Africa: An Investigation Based on the Perspectives of School Personnel - Li, Jiannan (Risk Manag Healthc Policy, 2020)
BACKGROUND: Schools in sub-Saharan Africa respond to the widespread use of tobacco among youth with the tobacco-prohibition policies. This study empirically examined the impact of the strength of campus tobacco-prohibition policies on tobacco use among youth across 20 sub-Saharancountries. METHODS: This study used data from the Global School Personnel Survey across 20 sub-Saharan countries during 2005–2011. Respondents comprised 7,365 school personnel (valid sample size) from Cameroon, Central African Republic, Congo, Eritrea, Ghana, Guinea-Bissau, Lesotho, Malawi, Mauritania, Mauritius, Namibia, Niger, Rwanda, Senegal, Seychelles, Sierra Leone, South Africa, Swaziland, Togo, and Uganda. Considering the potential endogeneity-estimation bias occurring in the normal ordinary least square estimation, instrumental variable estimation was used to ensure the regression results were reliable. RESULTS: The interaction term “tobacco-prohibition policy × policy-enforcement strength” was found to negatively predict perceived seriousness of tobacco use among youth (−0.0053, 95% CI [-0.0101, -0.0005]; p<0.05), which indicated that when campus tobacco-prohibition policy and enforcement were both sufficiently strict, the extent to which school personnel felt concerned or anxious about tobacco use among youth in the 20 countries was lowest. A series of identification tests using instrumental variable estimation demonstrated that these regression results were reliable and without endogeneity-estimation bias. CONCLUSION: This study confirms the effectiveness of the interaction of tobacco-prohibition policy and policy-enforcement strength for alleviating the seriousness of tobacco use among youth in underdeveloped areas. A series of important policy implications are discussed to prevent fast development of tobacco use in this area.